AKTivation of PI3K/AKT/mTOR signaling pathway by KSHV - Bhatt, Aadra P.; Damania, Blossom (Frontiers in Immunology, 2013)
As an obligate intracellular parasite, the Kaposi sarcoma-associated herpesvirus (KSHV) relies on host cell machinery to meet its needs for survival, viral replication, production, and dissemination of progeny virions. KSHV is a ɣ-herpesvirus that is associated with three different malignancies: Kaposi sarcoma (KS), and two B cell lymphoproliferative disorders, primary effusion lymphoma (PEL) and multicentric Castleman disease (MCD). KSHV viral proteins modulate cellular phosphatidylinositol-3-kinase (PI3K)/AKT/mammalian target of rapamycin (mTOR) signaling pathway, which is a ubiquitous pathway that also controls B lymphocyte proliferation and development. We review the mechanisms by which KSHV manipulates the PI3K/AKT/mTOR pathway, with a specific focus on B cells.